2012
DOI: 10.1007/s11606-012-2200-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Longitudinal Medication Non-Adherence on Mortality by Race/Ethnicity among Veterans with Diabetes

Abstract: OBJECTIVE:To examine the differential effect of medication non-adherence over time on all-cause mortality by race/ethnicity. RESEARCH DESIGN AND METHODS: Data on a longitudinal cohort of veterans with type 2 diabetes was examined. The main outcome was time to death. Primary independent variables were race/ethnicity and mean medication possession ratio (MPR) categorized into quintiles over the study period. Cox regression was used to model the association between time to death and MPR quintiles and race/ethnici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…Eight of the 12 studies testing unadjusted disparities found NHBs[6266; 68; 72] and, separately, Hispanics[62; 63; 6567] were less adherent in taking medications than NHWs. Three of the six studies testing adjusted disparities found NHBs[62; 68; 70] and, separately, Hispanics[62; 70] were less adherent to medications than NHWs.…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the 12 studies testing unadjusted disparities found NHBs[6266; 68; 72] and, separately, Hispanics[62; 63; 6567] were less adherent in taking medications than NHWs. Three of the six studies testing adjusted disparities found NHBs[62; 68; 70] and, separately, Hispanics[62; 70] were less adherent to medications than NHWs.…”
Section: Resultsmentioning
confidence: 99%
“…Low socioeconomic status, low health literacy, and racial/ethnic and cultural differences have been shown to play a role in nonadherence in several oncologic and nononcologic settings. [26][27][28][29][30][31] Thus, low health literacy explained the racial disparities in medication adherence among African-American youth with diabetes. 30 Furthermore, poor adherence among African Americans, Asian Americans, and Hispanics with hypertension improved by reducing patient copayments, improving access to medications, and optimizing choice of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…41 Furthermore, medication nonadherence is associated with an increase in all-cause mortality. 31 Although outpatient oral 6MP treatment is relatively inexpensive, salvage treatment of relapsed ALL is expensive, associated with extensive morbidity, and largely unsuccessful, thus creating a critical need to develop measures to enhance adherence to oral 6MP.…”
Section: Discussionmentioning
confidence: 99%
“…Binary indicators of co-morbidities were based on a positive response to a question “Have you ever been diagnosed with…” Cardio Vascular Disease (CVD) indicates a positive response to a question “Have you ever been diagnosed with coronary heart disease or angina or myocardial infarction or other heart diseases?” Previous studies showed that the binary indicator of disease is more effective in accounting for disease burden. (26, 27) Race/ethnic groups are categorized as: Non-Hispanic White (NHW), Non-Hispanic Black (NHB), Hispanic or others. Education was categorized as: less than high school (≤ grade 11), high school (grade 12) and college or more (grade ≥ 13).…”
Section: Methodsmentioning
confidence: 99%